2011
DOI: 10.3109/00016489.2011.580003
|View full text |Cite
|
Sign up to set email alerts
|

Association of air-conducted sound oVEMP findings with cVEMP and caloric test findings in patients with unilateral peripheral vestibular disorders

Abstract: The MD patients did not show a significant association between their ACS oVEMP findings and ACS cVEMP findings but there was an association of ACS oVEMP findings with caloric test findings. When the MD patients were classified into four stages based on their hearing levels, the patients showed abnormal findings at earlier stages on ACS cVEMP than on other tests. While all six VN patients showed abnormal findings on ACS oVEMP and caloric tests, only two patients showed abnormal ACS cVEMPs. These findings suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 23 publications
8
53
2
1
Order By: Relevance
“…The decreasing order of abnormal percentages for audiometry, ACS cVEMPs, BCV oVEMPs and caloric tests was reported to reflect dysfunction of the cochlea, saccule, utricle and semicircular canals which mimics the declining sequence of endolymphatic hydrops localization in the inner ear (Huang et al, 2011). Consistent with the aforementioned results, ACS cVEMPs were reported to deteriorate already in the earlier stage of MD, while ACS oVEMPs and caloric tests were affected in later stages (Murofushi et al, 2011).…”
Section: Menière's Diseasesupporting
confidence: 50%
See 1 more Smart Citation
“…The decreasing order of abnormal percentages for audiometry, ACS cVEMPs, BCV oVEMPs and caloric tests was reported to reflect dysfunction of the cochlea, saccule, utricle and semicircular canals which mimics the declining sequence of endolymphatic hydrops localization in the inner ear (Huang et al, 2011). Consistent with the aforementioned results, ACS cVEMPs were reported to deteriorate already in the earlier stage of MD, while ACS oVEMPs and caloric tests were affected in later stages (Murofushi et al, 2011).…”
Section: Menière's Diseasesupporting
confidence: 50%
“…Not only in vestibular neuritis, but also in Menière's disease, air-conducted cVEMPs and oVEMPs were not associated. In MD patients, ACS cVEMPs were reported to be abnormal, whereas ACS oVEMPs were sparsely affected, indicating a different origin of both myogenic potentials Murofushi et al, 2011). Similarly, bilaterally normal cVEMPs with unilateral absence of oVEMPs were reported in a patient with vestibular schwannoma .…”
Section: Utricle Vs Sacculementioning
confidence: 94%
“…Numerous studies have demonstrated that oVEMP was elicited via a contralateral excitatory potential. The likely pathway begins with the utricular macula, via the superior vestibular nerve, to the vestibular nuclei, the medial longitudinal fasciculus, the contralateral oculomotor nerve nuclei, until the brevissimus oculi (Rosengren et al, 2005;Todd et al, 2007;Iwasaki et al, 2008;Todd et al, 2008;Chihara et al, 2009a;Chihara et al, 2009b;Curthoys et al, 2009;Iwasaki et al, 2009;Smulders et al, 2009;Welgampola et al, 2009;Curthoys et al, 2011;Murofushi et al, 2011;Curthoys et al, 2012;Shin et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Cervical and ocular vestibular evoked myogenic potentials (cVEMP and oVEMP) were absent to the right ear stimulation (air-conducted 500 Hz short tone bursts, 125 dBSPL) ( Figure 2). Recording methods of VEMPs were the same as those by Murofushi et al [2]. He also complained of progression of his hearing loss, which was confirmed by pure tone audiometry ( Figure 1).…”
Section: Case Presentationmentioning
confidence: 60%